TINJAUAN YURIDIS TERHADAP PENDAFTARAN INDIKASI GEOGRAFIS PRODUK PERTANIAN DI SUMATERA UTARA - DESY PURNAMA SARI NAINGGOLAN (PREMISE LAW JURNAL, 2015)
Sumatera Utara is one of the provinces in Indonesia having several agricultural products which are potential to be the geographical indication. The agricultural product produced by each region in Indonesia have certain characteristic caused by the natural and human factyors or the combination of both of them which distinguish the agricultural product of the same kind originating from different regions in Indonesia. The purpose of this descriptive analytical normative juridical study was to describe and analyze the problems related to the registration of geographical indication of agricultural product in Sumatera Utara discussed in this study. The data for this study were the secondary data obtained through library research in the forms of the regulations or legal materials. Based on the result of this study, the conclusion is that: (1) Mandailing Coffee, Lintong Coffee, Sidikalang Coffee, Deli Tobacco, Binjai Rambutan are several agricultural products which are potential to be the geographical indication originating from several regions in Sumatera Utara, (2) the protection for geographical indication of agricultural product regulated by the law and government regulation is not yet effectively implemented, and (3) the constraints occured during the registration of geographical indication of agricultural products in Sumatera Utara in terms of regilations of legislation, role of government, and the farmers as the producers of georaphical-indicated agricultural products. Keywords: Intellectual Property Right, Geographical Indication, Agricultural Product